Central monitoring alarm system - Mahidin, Zuhairy (1994)
The purpose of this project is to design the hardware and to develop the software to centralised the fire alarm system. The existing fire detector alarm panel is equip with Charge Fail, A/C Fail, Battery Fail, Buzzer, Master Alarm, Alarm 1, Alarm 2 and Alarm 3. All this information will be centralised at a central control room. The circuit developed can detect the sensor status up to 512 locations with the selectable scanning rate of 9600 baud rate. The software has been program to detect the failure at each location. The failure will be highlighted on the personal computer screen by '*' symbol as an indicator. Therefore, the security officer will know the location of the failure. The software parts was done by using the Quick Basic high level language. Which is easy to understand and also make it easier for other people to develop and change the program for future modification.